Functional Genomics of PRUNE1 in Neurodevelopmental Disorders (NDDs) Tied to Medulloblastoma (MB) and Other Tumors - Bibbò, Francesca; Sorice, Carmen; Ferrucci, Veronica; Zollo, Massimo (Frontiers in Oncology, 2021)
We analyze the fundamental functions of Prune_1 in brain pathophysiology. We discuss the importance and maintenance of the Prune_1 function and how its perturbation influences both brain pathological conditions “neurodevelopmental disorder with microcephaly, hypotonia, and variable brain anomalies” (NMIHBA; OMIM: 617481) and tumorigenesis of Medulloblastoma (MB) with functional correlations to other tumours. A therapeutic view underlying recent discoveries identified small molecules and cell penetrating peptides to impair the interaction of Prune_1 with protein partners (e.g., Nm23-H1), thus further impairing intracellular and extracellular signaling (i.e., canonical Wnt and TGF-b pathways). Identifying the mechanism of action of Prune_1 as responsible for neurodevelopmental disorders (NDDs), we have recognized other genes which are found overexpressed in brain tumours (e.g., MB) with functional implications in neurodevelopmental processes, as mainly linked to changes in mitotic cell cycle processes. Thus, being Prune_1 a significant target in NDDs, we discuss how its network of action can be dysregulated during brain development, thus generating cancer and metastatic dissemination.